English - Bisama Mutshipayi, Gerard (Journal of Health Informatics in Africa, 2020)
Background and Purpose: Many countries intensify their efforts to implement and scale up health information systems to track health service utilization and to support various aspects of health system decision-making. Generally in Low and middle income countries, health data come from different Information systems implemented by different donors and focused on specifics health issues such as: maternal and child health, HIV/AIDS, Human Resources etc…where data that are related each others are represented in different formats, collected by different actors and reported in different way. Actually, some systems offer the capabilities to publish data in international standardized format such as Aggregated Data Exchange, Mobile Care Service Discovery but data exchange is not often taken into account in most implementation plan to build integrated National Health Information System Architecture. To avoid squandering the considerable efforts and resources allocated to implement and to sustain Health Information Systems, the need to put in place interoperability mechanism to exchange data is increasingly highlighted. Since 2014 when two majors Health Information Systems: District Health Information System 2 and integrated Human Resources Information System has been put in place in the Democratic Republic of Congo, some challenges appears to perform cross data analysis and reporting. Through this case study, the paper shows how the implementation of the interoperability layer within the National Health Information System architecture could be one of the solutions to solve the issue related to the cross data analysis and to improve the data use for better decision in the provision of a effective health services. Methods: Two methods to conduct the case study exploring the themes related to the adoption of interoperability within the national health strategy documents to build HIS framework in Democratic Republic of Congo. The document review of national strategic documents to determine how eHealth, health Information System are understood by policy makers and how important are those themes in building an effective Health System and then, the review of different narrative reports produce during the implementation and the use of integrated Human Resources Information System) and District Health Information System 2 to explored challenges and the opportunities to put in place interoperability mechanism. Results: Adoption of an interoperability model such as OpenHIE in the National Health Information Architecture will improve the use and the quality of data produced by iHRIS and DHIS2 by unifying the health information collected and maintained by many disparate individual organizations to support the decision making in the provision of better health services. Four use cases can be used as stating point to build an interoperability layer within the National Health Information System architecture. Conclusions: The Democratic Republic of Congo like other low and middle income countries requires strong and adaptive health systems at both the national and subnational levels to pursue the ambitious SDG 3 targets: Ensure healthy lives and promote well-being for all at all ages. To take advantage of the maximum benefit provides by digital health information systems and technologies, the Democratic Republic of Congo needs to integrate an Interoperability standard such OpenHIE in the National Health Information System framework to unify the health information collected and maintained by many disparate individual organizations to support decision making in the improvement of the quality and the productivity of operations within health care facilities.